2002
DOI: 10.1207/s15327914nc431_2
|View full text |Cite
|
Sign up to set email alerts
|

Types of Dietary Fat and Soy Minimally Affect Hormones and Biomarkers Associated With Breast Cancer Risk in Premenopausal Women

Abstract: Fourteen premenopausal women participated in a randomized, crossover controlled feeding study of three diets, each two menstrual cycles long. We compared a high saturated fat Western diet (control diet) with two other diets: the control diet plus soy protein (soy diet) and the control diet with polyunsaturated fat (PUFA diet) replacing most of the saturated fat. We measured reproductive and serum hormones, urinary estrogen metabolites and isoflavonoids, and menstrual cycle length. In the follicular phase, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 31 publications
1
52
0
Order By: Relevance
“…The results of the present study agree with some of the previous reports (2,4,9,23) that described an increase in the 2:16α-OH E 1 ratio and disagree with others (24,25) that observed no effect on the 2:16α-OH E 1 ratio after a soy intervention. The studies varied in feeding duration but were generally short-term (ranging from 1–3 menstrual cycles to 100 days) and mostly used soy protein or highly processed isoflavone-containing products.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the present study agree with some of the previous reports (2,4,9,23) that described an increase in the 2:16α-OH E 1 ratio and disagree with others (24,25) that observed no effect on the 2:16α-OH E 1 ratio after a soy intervention. The studies varied in feeding duration but were generally short-term (ranging from 1–3 menstrual cycles to 100 days) and mostly used soy protein or highly processed isoflavone-containing products.…”
Section: Discussionsupporting
confidence: 83%
“…In one 2-month intervention study with 62 women a significant reduction was observed in luteal estradiol and estrone levels among wheat-bran but not oat- or corn-bran supplements groups [66]. However, two other dietary intervention studies (using a 12-month low-fat/high-fiber intervention among 213 women [67] or a 2-month replacement of saturated fat with polyunsaturated fat among 14 women [68]) found no influence of diet change on blood estrogen levels in the luteal [67, 68] or follicular [68] phases. Several cross-sectional studies found significant positive associations between total and monounsaturated fat intakes and follicular estrone levels [69] or inverse associations between the ratio of polyunsaturated to saturated fat (P/S) and estradiol and estrone during the luteal phase [70], or higher follicular plasma estrogen levels among high-fat/low-fiber group [71].…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies found significant positive associations between total and monounsaturated fat intakes and follicular estrone levels [69] or inverse associations between the ratio of polyunsaturated to saturated fat (P/S) and estradiol and estrone during the luteal phase [70], or higher follicular plasma estrogen levels among high-fat/low-fiber group [71]. In other studies, no significant associations were observed between dietary fiber intakes and estrogen levels during the follicular [69, 70] or luteal [68, 70] phases. Cumulatively, no strong consistent associations have been observed, and weak to moderate effects remain uncertain; our study, which is substantially larger than previous cross-sectional studies, suggests there is little, if any, association between these macronutrients and premenopausal estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 18 RCTs assessed circulating estrogens levels (E1, E2, and/ or E3) Fifteen of 18 studies found no significant impact from soy compared to the control group (p>0.05) [129,132,133,138,140,143,145,147,149,150,155,156,158,160,163]. Three studies found a significant reduction in circulating estrogens compared to the control group (p<0.05) [151,153,155].…”
Section: Resultsmentioning
confidence: 99%